Particle fluxes and their drivers in the Avilés submarine canyon and adjacent slope, central Cantabrian margin, Bay of Biscay. (May 2016) - Rumín-Caparrós, A.; Sanchez-Vidal, A.; González-Pola, C.; Lastras, G.; Calafat, A.; Canals, M.
Highlights: Avilés Canyon is one of the largest submarine canyons in Europe. Total mass fluxes are dominated by river-sourced lithogenics (53–67%). Biological inputs account in average for more than 30% of the total mass flux. Wind regime, storms and tides drive sediment dynamics in the canyon. No seasonal signal is found in mass fluxes in the middle–lower canyon reaches. Abstract: The Avilés Canyon in the central Cantabrian margin is one of the largest submarine canyons in Europe, extending from the shelf edge at 130 m depth to 4765 m depth in the Biscay abyssal plain. In this paper we present the results of a year-round (March 2012 to April 2013) study of particle fluxes in this canyon and the adjacent continental slope. Three mooring lines equipped with automated sequential sediment traps, high-accuracy conductivity-temperature recorders and current meters allowed measuring total mass fluxes and their major components (lithogenics, calcium carbonate, opal and organic matter) in the settling material jointly with a set of environmental parameters. The integrated analysis of the data obtained from the moorings together with remote sensing images and meteorological and hydrographical data has shed light on the sources of particles and the across- and along margin mechanisms involved in their transfer to the deep. Our results allow interpreting the dynamics of the sedimentary particles in the study area. Two factors play a critical role: (i) direct delivery of river-sourced material to the narrow continental shelf, and (ii) major resuspension events caused by large waves and near bottom currents developing at the occasion of the rather frequent severe storms that are typical of the Cantabrian Sea. Wind direction and subsequent wind-driven currents largely determine the way sedimentary particles reach the canyon. While westerly winds favour the injection of sediments into the Avilés Canyon mainly by building an offshore transport in the bottom Ekman layer, easterly winds ease the offshore advection of particulate matter towards the Avilés Canyon and its adjacent western slope principally through the surface Ekman layer. Furthermore, repeated cycles of semidiurnal tides add an extra amount of energy to the prevailing bottom currents and actively contribute to keep a permanent background of suspended particles in near-bottom waters. High contents of lithogenics in settling particles at the three mooring stations confirm that riverine inputs are the principal source of particles to the Avilés Canyon, including the lowermost canyon, and the adjacent open slope. Primary production also has a strong influence on the amount and the composition of particulate matter, with more than 30% of the total mass flux being of biogenic origin (organic matter, opal and calcium carbonate).